Application of job scheduling in small scale rice milling firm (2010)
Rice is the edible seed of a plant which is a member of the grass family. It is an annual plant which is grown in many countries throughout the world and is the staple diet for over half the world's population. Rice milling firm has therefore occupied a significant position in the small,medium and large scale enterprises of many nations. In application of job scheduling in rice milling activities a framework for proper scheduling of activities (jobs) in rice milling processing firm in Nigeria has been developed. The methodology addresses this problem by supposing we have (n) customers to be served (where n is large); in what way should customers' order be processed such that the firm's profit is maximized while the customers are not unnecessarily delayed? The problem is addressed by using makespan as a measure of performance while the job orders were sequentially scheduled according to order of priority to achieve optimum results. The results show that CDS and A1 heuristics are preferred to the traditional method or USO. Accordingly, the CDS heuristic followed by A1 heuristic gives the best makespan result.